АТРОФ ТАБИИЙ МУҲИТНИ РАДИАЦИЯ ТАЪСИРИДАН ҲУҚУҚИЙ МУҲОФАЗА ҚИЛИШДА ЭКОЛОГИК ЭКСПЕРТИЗАНИНГ ЎРНИ ВА РОЛИ - Бабаназаров, К.Р. (SCIENCE and SOCIETY, 2016)
In the article features of environmental assessment in the sphere of radiation safety are studied. The article is devoted to the order of carrying out and methods of assessment in the sphere of environmental assessment.
Keywords: radiation safety; environmental assessment; objects of dangerous production; criteria and methods of environmental assessment